"This Nation Has Never Honestly Dealt with the Question of a Peacetime Economy": Coretta Scott King and the Struggle for a Nonviolent Economy in the 1970s. Issue 1 (14th March 2016) - Stein, David P.
Abstract : This article highlights the work of Coretta Scott King in the struggle for governmental guarantees to employment in the 1970s. In the two decades after her husband's death, Scott King devoted herself to achieving governmental guarantees to employment and disentangling militarism and violence from the economy. For her, this was the continuation of the civil rights movement. Considering the efforts of Scott King highlights the class content of the long civil rights struggle after the 1960s and the contested evolution of neoliberalism. Further, focusing on the unsuccessful efforts of Scott King also reveals the difficulty of achieving legislation to ameliorate the crisis of unemployment, and how racism and patriarchy structured labor markets during this period.